Methodology of ECG Interpretation in the Glasgow Program - Macfarlane, P. W.; Devine, B.; Latif, S.; McLaughlin, S.; Shoat, D. B.; Watts, M. P. (Methods of Information in Medicine, 1990)
This paper describes the methods currently used in Glasgow Royal Infirmary for computer analysis of electrocardiograms. The software is designed to analyse from 3 to 15 simultaneously recorded leads, with facilities for analysis of rhythm and serial changes. Options for Minnesota Code (with serial comparison) and XYZ lead interpretation are available.
Keywords: Computer Analysis; Electrocardiogram